2020
DOI: 10.1097/inf.0000000000002862
|View full text |Cite
|
Sign up to set email alerts
|

A Multicentered Study on Epidemiologic and Clinical Characteristics of 37 Neonates With Community-acquired COVID-19

Abstract: Background: Coronavirus disease 2019 (COVID-19) primarily affects adults and spares children, whereas very little is known about neonates. We tried to define the clinical characteristics, risk factors, laboratory, and imagining results of neonates with community-acquired COVID-19. Methods: This prospective multicentered cohort study included 24 neonatal intensive care units around Turkey, wherein outpatient neonates with COVID-19 were registered in an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 35 publications
4
54
2
7
Order By: Relevance
“…Accumulating evidence with regard to treatment of COVID-19 in early life indicates that very few neonates require additional treatment, with antiviral agents, azithromycin, or a-interferon which reflects the current uncertainties regarding specific treatment options [3,9,12]. All our patients were, rapidly improved without any specific treatment, providing further evidence that additional treatment is not necessary for a favor outcome of community-acquired COVID-19 in neonates and very young infants.…”
Section: Table 1 Epidemiological and Clinical Characteristics Of Infamentioning
confidence: 62%
See 1 more Smart Citation
“…Accumulating evidence with regard to treatment of COVID-19 in early life indicates that very few neonates require additional treatment, with antiviral agents, azithromycin, or a-interferon which reflects the current uncertainties regarding specific treatment options [3,9,12]. All our patients were, rapidly improved without any specific treatment, providing further evidence that additional treatment is not necessary for a favor outcome of community-acquired COVID-19 in neonates and very young infants.…”
Section: Table 1 Epidemiological and Clinical Characteristics Of Infamentioning
confidence: 62%
“…Neutropenia and/or monocytosis was detected in 10 infants (71.4%) while none of them experienced lymphopenia which has consistently been reported in adults and has been associated with increased disease severity [9]. The lack of lymphopenia, possibly attributed to the high thymic output in early life, in association with the relative immaturity of monocytes which results in diminished cytokine responses, could be a smart way of the neonatal immune system to response to SARS-CoV-2 without excessive inflammation associated with severe lung disease [10].…”
Section: Table 1 Epidemiological and Clinical Characteristics Of Infamentioning
confidence: 64%
“…Nine studies 21, 24, 27, 29, 31, 33, 36, 39, 42 included children with brain-based disabilities, and the remaining 20 included children at risk of developing a brain-based disability (premature infants and infants with congenital heart diseases in most studies) (Table 2). Most studies were published in the United States and the majority of studies were case reports or case series (23/29, 79%).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 104 included studies, mainly observational retrospective, 42 were reporting results from China (19-60), 19 from the U.S.A (61-79), 5 from the U.K (80-84), 24 across Europe, mainly Italy, Spain, France and the Netherlands (85-109), 10 from other countries (110-119) and 3 were international (120-122). All studies reported data on hospitalized patients due to COVID-19 and 35 of them included data for ICU nnnnnn(20, 25, 33, 36, 37, 41, 44, 45, 48, 52, 53, 56, 58, 66, 72, 73, 81-84, 86-89, 95, 96, 98, 101, 103, 106, 107, 109, 111, 119). Eight studies were pediatric (59, 60, 78, 79, 83, 84, 118, 119).…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported data on hospitalized patients due to COVID-19 and 35 of them included data for ICU nnnnnn(20, 25, 33, 36, 37, 41, 44, 45, 48, 52, 53, 56, 58, 66, 72, 73, 81-84, 86-89, 95, 96, 98, 101, 103, 106, 107, 109, 111, 119). Eight studies were pediatric (59, 60, 78, 79, 83, 84, 118, 119). The majority of articles included patients without any selection criteria (all-comers), whereas forty-five focused on specific subgroups, such as critically ill, cancer or rheumatologic patients, patients on mechanical ventilation etc.…”
Section: Resultsmentioning
confidence: 99%